2011
DOI: 10.3109/1547691x.2011.613419
|View full text |Cite
|
Sign up to set email alerts
|

A predictive biomimetic model of cytokine release induced by TGN1412 and other therapeutic monoclonal antibodies

Abstract: Human peripheral blood mononuclear cells (PBMC) are routinely used in vitro to detect cytokine secretion as part of preclinical screens to delineate agonistic and antagonistic action of therapeutic monoclonal antibodies (mAbs). Preclinical value of standard human PBMC assays to detect cytokine release syndrome (CRS) has been questioned, as they did not predict the "cytokine storm" that occurred when healthy human volunteers were given a CD28-specific super-agonist mAb, TGN1412. In this article, we describe a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…In vitro modelling of antigenicity utilizes T cell assays, B cell assays, and mimotopes to identify potentially immunogenic epitopes [33, 34], whereas in vitro characterization of immunogenic response from serum samples includes qualitative and quasiquantitative immunoassays such as enzyme linked immunosorbent assays (ELISAs), radioimmunoassays (RIAs), and immunoradiometric assays (IRMAs) [35]. Cell-based assays remain a popular choice for modeling antigenicity via the immunophenotyping, proliferation tracking, and cytokine secretion profiling of immune cells [36, 37].…”
Section: Immunogenic Risk Factors and The Need For Predictive Toolsmentioning
confidence: 99%
“…In vitro modelling of antigenicity utilizes T cell assays, B cell assays, and mimotopes to identify potentially immunogenic epitopes [33, 34], whereas in vitro characterization of immunogenic response from serum samples includes qualitative and quasiquantitative immunoassays such as enzyme linked immunosorbent assays (ELISAs), radioimmunoassays (RIAs), and immunoradiometric assays (IRMAs) [35]. Cell-based assays remain a popular choice for modeling antigenicity via the immunophenotyping, proliferation tracking, and cytokine secretion profiling of immune cells [36, 37].…”
Section: Immunogenic Risk Factors and The Need For Predictive Toolsmentioning
confidence: 99%
“…Attempts to model in vivo presentation of TGN1412 employed a co-culture of human endothelial cell monolayers with donor lymphocytes have been shown to result in pro-inflammatory cytokine release, particularly IL-6, IL-8, and TNF α (Stebbings et al, 2007; Findlay et al, 2011b; Dhir et al, 2012). It has subsequently been reported that the cytokine profile of this model does not fully match that of the trial volunteers or assays with immobilized TGN1412, as only low levels of the cytokines IL-2 and IFN γ are produced (Findlay et al, 2011b).…”
Section: Assay Refinements and Co-culture Alternativesmentioning
confidence: 99%
“…Recently, several groups have published on in vitro assays that may offer predictivity for in vivo cytokine release (Dhir et al 2012;Findlay et al 2011).…”
Section: Cytokine Releasementioning
confidence: 99%